Verbascum shahsavarensis (Scrophulariaceae), a new species for Flora of Iran - Sotoodeh, Arash; Civeyrel, Laure; Attar, Farideh (Phytotaxa, 2015)
A new endemic species, Verbascum shahsavarensis, is described from north of Iran. Based on two unique characters of this species, these being two anterior longitudinally obliquely inserted anthers and an ebracteolate pedicel, we compared it to species described by Murbeck in 1933. The new species can be easily distinguished from the other Iranian species by having bi-colored hairs on the stamen filaments and the unique anther and pedicel characters. A distribution map is provided. The name of new species comes from Shahsavar, the ancient name of Tonekabon, an old coastal city on the Caspian Sea.